2017
DOI: 10.1007/s10340-017-0878-4
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Monochamus galloprovincialis, the European vector of the pinewood nematode

Abstract: We reconstructed the phylogeography of European populations of Monochamus galloprovincialis (Coleoptera, Cerambycidae), the European vector of the pinewood nematode, Bursaphelenchus xylophilus. This study investigated the Quaternary history of M. galloprovincialis and tested whether environmental parameters and/or host tree species influenced the genetic structure of M. galloprovincialis populations. Twelve polymorphic microsatellite loci and a Bayesian analysis were applied to 1098 individuals of M. galloprov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Mantel tests and a commonality analysis supported the hypothesis that elevated areas and their associated colder temperatures constitute barriers to gene flow for M. galloprovincialis . This result corroborates the observations made for the congeneric species M. alternatus across the Ohu chain of mountains in Japan ( Shoda-Kagaya, 2007 ) and on M. galloprovincialis across the Pyrenees ( Haran et al, 2015 ; Haran et al, 2017 ). In addition, this hypothesis tends to be confirmed by several studies showing that M. galloprovincialis larva development and survival ( Naves & De Sousa, 2009 ), and its ability to complete its development within one or two years ( Tomminen, 1993 ; Naves et al, 2007 ; Koutroumpa et al, 2008 ), are affected by low temperatures.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Mantel tests and a commonality analysis supported the hypothesis that elevated areas and their associated colder temperatures constitute barriers to gene flow for M. galloprovincialis . This result corroborates the observations made for the congeneric species M. alternatus across the Ohu chain of mountains in Japan ( Shoda-Kagaya, 2007 ) and on M. galloprovincialis across the Pyrenees ( Haran et al, 2015 ; Haran et al, 2017 ). In addition, this hypothesis tends to be confirmed by several studies showing that M. galloprovincialis larva development and survival ( Naves & De Sousa, 2009 ), and its ability to complete its development within one or two years ( Tomminen, 1993 ; Naves et al, 2007 ; Koutroumpa et al, 2008 ), are affected by low temperatures.…”
Section: Discussionsupporting
confidence: 91%
“…To model resistance based on pine density, we considered the sum of densities of all pine species encountered in a grid cell, because in the Iberian Peninsula, M. galloprovincialis shows no preference for pine species. As shown in previous studies, this beetle will live in the dead wood of any of the pine species considered in this study ( Pinus pinaster, P. nigra, P. sylvestris, P. halepensis and P. radiata ; Naves, Sousa & Quartau, 2006 ; Haran et al, 2015 ; Haran et al, 2017 ). Resistance to dispersal was also modeled as a function of the mean minimum temperature (and its proxy: elevation, hereafter called scenarios T and E respectively), as low summer temperatures tend to inhibit adult flying activity ( Hernández et al, 2011 ), and because low winter temperatures are likely to determine the survival or the development rate of M. galloprovincialis larval instars ( Naves, Sousa & Quartau, 2006 ).…”
Section: Methodsmentioning
confidence: 63%
“…The study of the intraspecific diversity within the genus Monochamus is still largely in progress. For example, a recent work by Haran et al (2017) using polymorphic microsatellites and samples from 45 European locations has shown that five distinct populations of M. galloprovincialis exist in Europe. On the other hand, this study did not find any support to validate the distinction between two subspecies made so far in Europe (e.g.…”
Section: Intraspecific Diversitymentioning
confidence: 99%
“…Healthy and slightly weakened trees can decline because of maturation feeding of some stem insects, particularly Tomicus piniperda (Linnaeus, 1758), Tomicus minor (Hartig, 1834) and Monochamus galloprovincialis (Olivier, 1795) (Meshkova and Nazarenko 2009;Meshkova et al 2017), and because of their ability to vector the pathogens (Davydenko et al 2014(Davydenko et al , 2017, particularly pinewood nematode, Bursaphelenchus xylophilus (Steiner & Buhrer, 1934) (Nickle 1970;Haran et al 2018).…”
Section: Introductionmentioning
confidence: 99%